Idosos e jogos digitais: uma contribuição para um envelhecimento ativo - MONTEIRO, Evandro de Souza (2019)
Digital games are able to provide bigger technological interactions, leisure and motivation to the elderly and, besides that, the benefit of maintaining and stimulating cognitive functions. However, so these benefits can be reached, it is necessary that the games take in consideration the particularities and limitations of each person which can be a result of one’s natural aging process. On this context, this paper aims to present an application for Android mobile devices called “Pará Memória”, a memory game developed focusing the elderly. This work describes the experience of the utilization of the game. For this project, it was made a qualitative research at the “Centro da Terceira Idade - Palácio Bolonha”, where courses are available only for the elderly, including a technology/computing course which was the research environment. On the first phase of this work, information was collected from 22 elders about how they would like the game to be, in order to meet their needs, specifically. The second part of the test was made with 8 elders through a practical experimentation with the game in order to collect the results. The interpretation of the information reunited on this project made possible to identify that it is possible to foster quality associating the game as a motivational entertainment and a cognitive abilities developer, working and encouraging the logical reasoning, the memory and the motor coordination, also bringing a bigger perception on the language domain when interacting with the mobile device.